PENERAPAN STRATEGI PEMBELAJARAN ACTIVE KNOWLEDGE SHARING UNTUK MENINGKATKAN MINAT DAN KOMUNIKASI MATEMATIS PESERTA DIDIK - Mira Meirani (UJMES (Uninus Journal of Mathematics Education and Science), 2017)
The background of this research was the low of students’ interest and mathematical communication ability. One of learning alternatif that can be applied to increase students’ interest and mathematical communication ability was the Active Knowledge Sharing learning strategy. The aims of this study to increase students’ interest and mathematical communication ability through Active Knowledge Sharing learning strategies, and students' responses to mathematics learning by using Active Knowledge Sharing learning strategies. The approach used in this research were qualitative and quantitative approach. While the method used in this research was Class Action Research method which refers to the steps of Kemmis and Mc Taggart model. A cycle consists of planning, implementation of action, observation, and reflection. The subject of this research was all of the student in VII-B class MTs at Pangalengan District, Bandung Regency. The data collection instruments consist of formative tests, observation sheets, questionnaires, and journals. Data analysis technique used Triangulation. Based on the results of the analysis that has been done, showed students’ interest and mathematical communication ability has increase after using the Active Knowledge Sharing learning strategy, and students’ response to mathematics learning by using Active Knowledge Sharing learning strategy is positive.